CD4 T Helper Type 1 and Regulatory T Cells Induced against the Same Epitopes on the Core Protein in Hepatitis C Virus-Infected Persons - MacDonald, Angus J.; Duffy, Margaret; Brady, Miriam T.; McKiernan, Susan; Hall, William; Hegarty, John; Curry, Michael; Mills, Kingston H. G. (The Journal of infectious diseases, 2002)
The factors that determine persistence or clearance of hepatitis C virus (HCV) infection are poorly understood. The CD4 T cell responses to the HCV core protein were examined in a cohort of women infected with a single genotype of HCV. CD4 T cells from HCV-infected patients secreted interferon (IFN)-γ in response to peptides from 4 immunodominant regions of the core protein, and these responses were stronger in persistently infected women. Interleukin (IL)-10 was also produced by CD4 T cells from HCV-infected subjects in response to the same core peptides. Furthermore, HCV core-specific CD4 T cell clones secreted either IFN-γ or IL-10 but not IL-4. These findings demonstrate that T helper type 1 and regulatory T cells are induced against the same epitopes on the core protein during HCV infection.